Experimental and analytical bond behaviour of masonry strengthened with steel reinforced grout (SRG) - Salsavilca, J.; Yacila, J.; Tarque, N.; Camata, G. (Elsevier, 2020)
Steel Reinforced Grout (SRG) is gaining popularity as a retrofitting system for structural elements due to advantages such as its effectiveness and ease of installation. The good performance of SRG system has turned out to be substantially dependent on the behaviour of the bond between the composite layer and the substrate. This paper presents an experimental study of the bond behaviour of Peruvian masonry strengthened with SRG, along with a characterization of the materials by means of direct tensile tests on the fiber and compression tests on the mortar. The criteria of the sample’s geometry, construction and test procedure are discussed for each trial since up to now there has been a gap in the standards that control them. In addition, an analytical model is employed in order to obtain design bond parameters to define a Cohesive Material Law (CML). The strain profile, slip profile, force profile and shear stress profile along the length of the bond are presented for each bond test. Finally, an optimal bond length is proposed for SRG material and a fracture energy value at the matrix-fiber interface
Keywords: Confined Masonry (CM); Steel Reinforced Grout (SRG); https://purl.org/pe-repo/ocde/ford#2.01.04